2020
DOI: 10.3390/sym12111767
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Interactions between Asphaltene and Surfactants in a Hydrocarbon Solvent: Application to Asphaltene Dispersion

Abstract: Heavy oil and bitumen supply the vast majority of energy resources in Canada. Different methods can be implemented to produce oil from such unconventional resources. Surfactants are employed as an additive to water/steam to improve an injected fluid’s effectiveness and enhance oil recovery. One of the main fractions in bitumen is asphaltene, which is a non-symmetrical molecule. Studies of interactions between surfactants, anionic, and non-anionic, and asphaltene have been very limited in the literature. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 84 publications
(82 reference statements)
0
13
0
Order By: Relevance
“…In the radial distribution function curve, there will appear a peak when molecules are ordered proximally in the r range. The sharper the peak, the more ordered the arrangement among molecules and the stronger the connection and the interaction. Figure shows the radial distribution function of SDBS molecule head groups at different concentrations in the crude oil/SDBS/mineral water systems and the crude oil/SDBS/pure water systems after dynamic relaxation equilibrium. It can be found that the peak value of the radial distribution function is small at low SDBS concentration, and with the increase in the SDBS concentration, the peak value of the radial distribution function increases.…”
Section: Resultsmentioning
confidence: 99%
“…In the radial distribution function curve, there will appear a peak when molecules are ordered proximally in the r range. The sharper the peak, the more ordered the arrangement among molecules and the stronger the connection and the interaction. Figure shows the radial distribution function of SDBS molecule head groups at different concentrations in the crude oil/SDBS/mineral water systems and the crude oil/SDBS/pure water systems after dynamic relaxation equilibrium. It can be found that the peak value of the radial distribution function is small at low SDBS concentration, and with the increase in the SDBS concentration, the peak value of the radial distribution function increases.…”
Section: Resultsmentioning
confidence: 99%
“…They also studied the behavior of nonionic and anionic surfactants as asphalt dispersants in hydrocarbon solvents. [ 50 ] The results showed that the molecular size of asphaltene was one of the main factors affecting the effect of surfactant dispersant. Increasing the molecular size of asphaltenes reduces the performance of surfactant dispersants.…”
Section: Basic Theory Of Foam and Mechanism Of Steam Foam Eormentioning
confidence: 99%
“…(2) We optimized the molecular model geometrically by the smart algorithm and gained the lowest energy configuration, then built an amorphous unit cell of 50 molecules with periodic boundary conditions by the amorphous cell module to ensure that the length of the unit cell was two times the cutoff radius. e initial density of the amorphous cell was set as 0.6 g/ cm 3 to ensure each molecule was distributed randomly [37].…”
Section: Force Field and Simulation Initializationmentioning
confidence: 99%